Study on radical dianions of carboxylates used as ligands of metal oxide nanocluster resists. (17th June 2021) - Ikeuchi, Kengo; Muroya, Yusa; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke; Kozawa, Takahiro
Abstract: Metal oxide nanocluster resists have recently attracted considerable attention for use in extreme ultraviolet lithography. In this study, radiation-induced reactions of carboxylic acids used as the ligands of metal oxide nanocluster resists were investigated using a pulse radiolysis method. Upon the irradiation of the aqueous solutions of calboxylic acids with an electron beam, radical dianions of carboxylates were generated under the basic condition. From the comparison between pulse radiolyses under acidic and basic conditions, the kinetics of the radical dianions was clarified. For aromatic carboxylates, anion radicals of carboxylic acids were generated through the reaction of their dianions with H2 O. For unsaturated carboxylates, their radicals were generated through the reaction of their radical dianions with H2 O. The carboxylic anions and vinyl groups were protonated for dianions of aromatic and unsaturated carboxylates, respectively. The proton dynamics control is important for the stable performance of metal oxide nanocluster resists.